2013
DOI: 10.1073/pnas.1201753109
|View full text |Cite
|
Sign up to set email alerts
|

Impaired epithelial differentiation of induced pluripotent stem cells from ectodermal dysplasia-related patients is rescued by the small compound APR-246/PRIMA-1 MET

Abstract: Ectodermal dysplasia is a group of congenital syndromes affecting a variety of ectodermal derivatives. Among them, ectrodactyly, ectodermal dysplasia, and cleft lip/palate (EEC) syndrome is caused by single point mutations in the p63 gene, which controls epidermal development and homeostasis. Phenotypic defects of the EEC syndrome include skin defects and limbal stem-cell deficiency. In this study, we designed a unique cellular model that recapitulated major embryonic defects related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 30 publications
3
65
0
2
Order By: Relevance
“…One example is the compound PRIMA-1 that restores wild-type conformation by binding to the core of mutant p53 and induces massive apoptosis in human tumor cells [145]. The PRIMA-1 analog APR-246 is currently in a clinical trial [146–148]. Very recently, another small molecule rescuer of mutant p53 was reported [149].…”
Section: Discussionmentioning
confidence: 99%
“…One example is the compound PRIMA-1 that restores wild-type conformation by binding to the core of mutant p53 and induces massive apoptosis in human tumor cells [145]. The PRIMA-1 analog APR-246 is currently in a clinical trial [146–148]. Very recently, another small molecule rescuer of mutant p53 was reported [149].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with APR-246 partially rescued morphology and gene expression during epidermal stratification, and restored expression of p63-regulated genes [32]. Also, APR-246 was shown to revert corneal epithelial lineage commitment and restore a normal p63-related signaling pathway in induced pluripotent stem cells (iPSC) from EEC patients carrying two different point mutations in the DNA binding domain of p63 [33]. The reactivation of mutant forms of p53 family proteins by APR-246 indicates a common mechanism that presumably involves homologous structural elements in the targeted proteins.…”
Section: Small Molecules That Target Mutant P53mentioning
confidence: 99%
“…To date, human iPSCs have been generated for several genetic skin disorders, including type VII collagen (Col7)-deficient Recessive Dystrophic EB (RDEB) (Itoh et al 2011; Tolar et al 2011), LAMB3 gene-deficient Junctional EB (JEB) (Tolar et al 2013), p63 mutant Ectrodactyly, Ectodermal dysplasia, and Cleft lip/palate (EEC) syndrome (Shalom-Feuerstein et al 2013), Epidermolytic Hyperkeratosis (EHK) with a dominant N188S keratin 1 mutation (Bilousova et al 2011b), and EB simplex (EBS) with a dominant R125C keratin 14 mutation (Bilousova et al 2012). In addition, iPSCs have been obtained from patients with Dyskeratosis Congenita (DC), a disease of telomere maintenance that manifests itself in multiple organ failures, cancer, and age-associated skin phenotypes such as dyskeratotic nails, delayed wound healing, and hair loss (Agarwal et al 2010; Agarwal and Daley 2011; Batista et al 2011).…”
Section: Application Of Ipscs In Dermatologymentioning
confidence: 99%
“…Mouse iPSC-derived keratinocytes were shown to form an epidermis and skin appendages when grafted with mouse fibroblasts onto athymic nude mice (Bilousova et al 2011a), whereas human iPSC-derived keratinocytes were able to establish a functional organotypic skin in culture (Itoh et al 2011). Keratinocytes were also generated from RDEB-iPSCs (Itoh et al 2011), JEB-iPSCs (Tolar et al 2013), EEC-iPSCs (Shalom-Feuerstein et al 2013), and EBS-iPSCs (Bilousova et al 2012) and were shown to recapitulate the phenotypes of corresponding diseases when grown in vitro . Melanocytes can be derived from iPSCs by supplementing the culture with Wnt3a, Stem Cell factor, and Endothelin-3 (Ohta et al 2011), and the treatment of iPSC cultures with EGF and BMP4 can produce fibroblasts (Hewitt et al 2011).…”
Section: Application Of Ipscs In Dermatologymentioning
confidence: 99%